The emergence of low-carbon community as an important concept to tackle the climate change - Abas, Ani Shazwani; Mohd Yunos, Mohd Yazid; Ismail, Sumarni; Utaberta, Nangkula; Ismail, Nor Atiah; Mohd Arifin, Noor Fazamimah (American-Eurasian Network for Scientific Information Publications(AENSI), 2015)
Background: It is widely documented that carbon dioxide (C[O.sub.2]) emissions due to anthropogenic activity are increasingly either causing or making climate change worse. The local community roles to decrease the impact of climate change has been broadly known in academia, as the local community is whose locally been directly impacted by the world climate change phenomenon. Herein, the emerging low-carbon community concept can be considered as crucial in tackling the climate change, particularly through community behavior change. Objective: Hence, this paper aims to present a review of low-carbon community concept, based on previous research by using the content analysis. Results: It is found that the low-carbon community was best to perform among local community as the concept will empower them towards establishing their own low-carbon activities. Conclusion: The paper concludes the importance of low-carbon community in tackling the climate change impact reduction and the key criteria towards low-carbon community, at the local level.